2017
DOI: 10.1016/j.vaccine.2017.03.081
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of thermostable vaccines

Abstract: Background While our previous work has shown that replacing existing vaccines with thermostable vaccines can relieve bottlenecks in vaccine supply chains and thus increase vaccine availability, the question remains whether this benefit would outweigh the additional cost of thermostable formulations. Methods Using HERMES simulation models of the vaccine supply chains for the Republic of Benin, the state of Bihar (India), and Niger, we simulated replacing different existing vaccines with thermostable formulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…The study reported that the addition of a prime-booster vaccine, applied at age 10, was more costsaving than a replacement vaccine applied only at birth, albeit with an assumed efficacy of 70%, as reflected in the net societal cost-saving results: USD 5.6 vs USD 3.6 million [32]. Similar findings were also reported by Knight et al, who demonstrated that a new TB vaccine targeting adolescents and adultswith 60% vaccine effectiveness and a 10year protection periodwould prevent more TB cases and yield lower ICER values than would a strategy targeting infants alone: 17 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) vs 0.89 (0.42-1.58) million TB cases prevented and USD 378 (USD 150-USD 881) vs USD 1,692 (USD 634-USD 4,603) per DALY averted, respectively [40]. It was also predicted that such investments in a better novel vaccine with an efficacy of 75% and a 10-year protection period would be profitable, with even higher values when considering productivity lost throughout the world setting [41].…”
Section: Economic Evaluation Of New Vaccinessupporting
confidence: 77%
See 1 more Smart Citation
“…The study reported that the addition of a prime-booster vaccine, applied at age 10, was more costsaving than a replacement vaccine applied only at birth, albeit with an assumed efficacy of 70%, as reflected in the net societal cost-saving results: USD 5.6 vs USD 3.6 million [32]. Similar findings were also reported by Knight et al, who demonstrated that a new TB vaccine targeting adolescents and adultswith 60% vaccine effectiveness and a 10year protection periodwould prevent more TB cases and yield lower ICER values than would a strategy targeting infants alone: 17 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) vs 0.89 (0.42-1.58) million TB cases prevented and USD 378 (USD 150-USD 881) vs USD 1,692 (USD 634-USD 4,603) per DALY averted, respectively [40]. It was also predicted that such investments in a better novel vaccine with an efficacy of 75% and a 10-year protection period would be profitable, with even higher values when considering productivity lost throughout the world setting [41].…”
Section: Economic Evaluation Of New Vaccinessupporting
confidence: 77%
“…An additional 10 studies were excluded due to partial evaluation; five evaluated only the cost and five described only the effectiveness of BCG vaccination. We further excluded one study that evaluated the effectiveness of BCG vaccine in chain distribution rather than explicitly considering the economic aspects [16], one study in which the input parameters for the economic evaluation of BCG vaccination program could not be retrieved [17], and one that did evaluate the costeffectiveness of BCG vaccination but that was rather a review than it was original research [18]. Details are provided in Figure 1.…”
Section: Article Highlightsmentioning
confidence: 99%
“…As it currently stands, all prequalified WHO vaccines require refrigeration ( 73 ). Nanovaccines may enable next-generation vaccines to be stored without the need for refrigeration (i.e., eliminating the cold chain), allowing for vaccines to be sent to remote locations in need for vaccination, resulting in reduced medical costs and productivity losses associated with disease ( 74 ). Previous work from our laboratories demonstrated that nanovaccines encapsulating PspA were able to retain protein structure and activity following release, and a nanovaccine encapsulating the Bacillus anthracis protective antigen (PA) released biologically and immunologically functional protein following storage at both room temperature and above after 4 months ( 28 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The need for thermostable vaccines is widely recognized. Failure of the cold-chain has often led to wasting of vaccines or administering despite loss of activity ( 93 ). Important advances have been made by optimizing the engineering and chemistry of vaccine formation.…”
Section: Adoption Of Catcher/tag Technology For Vaccine Assemblymentioning
confidence: 99%